KAJIAN AKTIVITAS ANTIDIABETES EKSTRAK ETANOL KULIT SALAK MANONJAYA (SALACCA ZALACCA (GAERTNER) VOSS VAR. ZALACCA) - Nur Azizah, Hilda
Diabetes mellitus is one of the most common disease in Indonesia. In 2014, there were 9.1 million people who suffer diabetes. Diabetes mellitus is a group of metabolic disorders that result in hyperglycemia due to decrease in insulin production and insulin sensitivity. In diabetes, hyperglycemia generates oxidative stress or increase free radical which cause insulin resistance and decrease in insulin production. Antioxidant has potential effect to prevent the destruction of pancreatic beta cell which inhibits the production of free radical chain reaction by binding to the free radical. The snake fruit peel stew has been used by some Indonnesian people to decrease blood sugar level. The aim of this research is to investigate the antidiabetic activity of the ethanolic extract of manonjaya snake fruit peel and the connection with its antioxidant activity. Crude drug of fruit snake peel was extracted by reflux using ethanol 96%. The parameter study involved in vivo and in vitro. Study in vivo involved glucose tolerance test, induction using alloxan monohydrate i.v (60 mg/kg BW), and histopathological. All in vivo study was conducted on male Swiss Webster mice model. Experimental animals were divided into six groups which are, negative control, positive control, snake fruit peel extract with dose of 125 mg/kg BW, 250 mg/kg BW, 500 mg/kg BW, and glibenclamide as a standard with dose of 0.65 mg/kg BW. In alloxan diabetic test, all animals were sacrificed after 21 days and the pancreas were isolated for histopathological tests. Study in vitro involved kualitative and kuantitative antioxidant activity test using DPPH. All the glucose tolerance tested groups and alloxan- induced diabetic groups which were treated with extract, their blood glucose level were significantly lower than positive control, indicating a potential effect as an antidiabetic agent. In alloxan-induced diabetic group, after 21 days of treatment, a group with extract at dose 500 mg/ kg BW showed the highest reduction percentage with a value of 37.29%. Extract showed strong antioxidant activity with IC50 of 0.778 µg/mL and standard ascorbic acid showed IC50 of 0.084 µg/mL. Ethanolic extract of snake fruit peel showed a potential effect as an antidiabetic on male Swiss Webster mice. Antidiabetic activity related to strong antioxidant activity of extract.